Assessment of Carbon Black Weight Fraction on the Shear Strength of Polyurethane Adhesive Joints - Muhamad Erlan Fahrizal; Sunardi Sunardi; Iman Saefuloh; Shofiatul Ula; Dwinanto Dwinanto; Irfan Santosa (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Adhesive bonding has become one of the most widely used joining techniques in engineering due to its ability to provide uniform stress distribution, minimize structural weight, and avoid the thermal distortion during welding processes. This study examines the effect of carbon black weight fraction on the shear strength of aluminum single-lap joints bonded with polyurethane adhesive. Aluminum 6061 specimens were prepared following ASTM D1002 standards and were reinforced with carbon black at weight fractions of 0, 8, 16, and 24 wt%. Fourier Transform Infrared (FTIR) spectroscopy was conducted to identify any chemical interactions, and lap shear testing was performed using a Universal Testing Machine (UTM). The results indicated that increasing the weight fraction of carbon black enhanced the shear strength and gradually shifted the failure mode from adhesive failure to cohesive failure. The specimen containing 24 wt% of carbon black exhibited the highest shear strength of 2.81 MPa, with 88% of the failures occurring cohesively. FTIR analysis revealed that carbon black did not introduce any new functional groups but functioned as a physical reinforcing filler within the polyurethane matrix. Therefore, carbon black is an effective reinforcing material for improving the mechanical performance of polyurethane adhesive-bonded aluminum single-lap joints.